POLA DAN PENGARUH PERDAGANGAN BILATERAL INDONESIA DENGAN KOREA SELATAN - Isnani, Mayafari Alawiyah; ', Rosyetti; ', Darmayuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the effect of the export price and the GDP of Indonesia to the volume of Indonesian exports to South Korea and see the pattern of bilateral trade between Indonesia and South Korea. The analytical method used is descriptive quantitative method. Analysis of partial and simultaneous with the classical assumption BLUE to see export prices and the effect of Indonesia's GDP to the volume of Indonesian exports to South Korea and the formula for the calculation of intra - industry Grubel and lyold to calculate the pattern of bilateral trade between Indonesia and South Korea. The results of multiple linear regression analysis in this study showed that the export price of significant positive effect on the volume of exports and GDP Indonesia significant positive effect on export volumes. Taken together the independent variables can explain the dependent variable for export function. Indonesia's bilateral trade with South Korea on the results of calculations using the formula intra - industry, it can be concluded that the pattern of industrial commodity trade between Indonesia and South Korea tend to be on the pattern of intra - industry trade, where the results of the calculation of GL index on average more than 40 % on commodities SITC 5-8 .Keywords : export prices, GDP, volume of Indonesian exports to South Korea, exports SITC 5-8 and imports SITC 5-8.